(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Latitudinal zonation of the moss flora was studied in the Koryakskoye Upland, situated in the extreme North-East of Russia where boreal habitats meet arctic habitats. The arctic fraction consists of the arctic, metaarctic and arctalpine geographical elements. Considerable participation of arctic fraction in the moss flora of Koryakskoye upland reflects northern mountain character of flora and its transition from arctic to boreal.